The Impact of Proactive Personality on Turnover Intention and Psychological Empowerment with the Mediating Role of Career Adaptability in the Context of the COVID-19 Pandemic among Snapp Company Employees in Iran - Kabiri, Azin; Golpour, Reza (Shahroud Journal of Medical Sciences, 2025)
Background: Career adaptability can help individuals see probabilities in unforeseen changes, invest in those changes, and improve unpredictable outcomes. On the other hand, career adaptability can be a double-edged sword and may lead to voluntary turnover intention. To better understand the concept of career adaptability and its role in an organization, the present study has focused on examining the impact of proactive personality on turnover intention and psychological empowerment with the mediating role of career adaptability in the context of the COVID-19 pandemic.Methods: This study employs a correlational method and is considered basic research from an objective standpoint. The administrative staff of Snapp company, who were 5000 individuals at the time of the study (2021), were selected as the statistical population, and 357 individuals were chosen as the sample based on Krejcie and Morgan Table. Due to the inability to access all individuals, sampling was done using the convenience sampling method. To assess proactive personality, the Bateman and Crant (1993) Proactive Personality Scale (α=0.909) was used. For measuring career adaptability the Savickas and Porfeli (2012) Career Adapt-Abilities Scale (α=0.843) was used. To measure turnover intention, the Kim et al. (2007) Turnover Intention Scale (α=0.809) was utilized, and to measure psychological empowerment the Spreitzer (1995) Psychological Empowerment Scale (α=0.898) was employed. The Kolmogorov-Smirnov test was used to choose the data analysis method. Due to the non-normality of the data, the structural equation modeling (and path analysis) technique was used to assess the causal relationship between variables.Results: Data analysis showed that there is a relationship between proactive personality and psychological empowerment of Snapp employees during the COVID-19 pandemic, with the mediating role of career adaptability (β=0.370). Additionallythere is a significant positive relationship between proactive personality and turnover intention (β=0.211) and psychological empowerment (β=0.557). Furthermore, the career adaptability of employees is significantly positively related to their psychological empowerment (β=0.438).Conclusions: Despite this, contrary to previous research, the results obtained in the current study did not show a relationship between career adaptability and turnover intention, and in the same way, rejected the mediating role of career adaptability in the mentioned relationship.